The COVID-19 pandemic: The importance of being alert to zoonoses.: La pandemia de COVID-19: Importancia de estar alerta ante las zoonosis. - E. Cortés, Manuel (2020)
The pandemic of Coronavirus Disease - 2019 (COVID) has produced hundreds of thousands of deaths and millions of infected people worldwide, with the consequent collapse of health systems. SARS-CoV-2, the coronavirus causing COVID-19, is a pathogen with a zoonotic origin. The objective of this article is to highlight the importance of being alert to zoonoses, with special reference to COVID-19. First, the general chronology of the COVID-19 pandemic is described, then the characteristics of the coronaviruses are described in detail, especially regarding those of SARS-CoV-2. Subsequently, the One Health concept is highlighted as an appropriate approach to face this zoonosis and other related ones. Furthermore, the importance of unequivocally identifying the SARS-CoV-2 reservoir and intermediate animals as part of the knowledge necessary to develop treatments and a vaccine for COVID-19 and related diseases is highlighted. It is concluded that it is important that the One Health approach be known, communicated and integrated by all health centres and health professionals because, considering the severity of zoonoses such as COVID-19, we should not forget that human health is linked to animal health, and both with environmental health. Finally, it is recommended that health agencies maintain preventive measures and personal distancing to avoid more infections.